Bentuk Komunikasi Transendental Terhadap Implikasi Bagi Kehidupan Manusia - Ach. Atikul Ansori (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2026)
This study aims to explain the phenomenon of tawhid as the foundation of transcendental communication from an Islamic perspective, encompassing the theological, philosophical, and epistemological dimensions of communication. This research employs a qualitative-descriptive approach using literature analysis of various classical and contemporary Islamic sources relevant to the concepts of tawhid and communication. Through this approach, the study seeks to identify the correlation between divine consciousness (tawhid) and human communication processes as spiritual activities. The findings indicate that tawhid is not merely a religious doctrine but also an epistemological paradigm that positions God as the central orientation of communication (theocentric paradigm). Within this framework, communication is understood as a process of divine awareness that connects human beings with God, the self, and others, while embodying moral and prophetic ethical values. The study further affirms that the tawhid paradigm can reconstruct modern communication theories, which tend to be anthropocentric, toward a more holistic and transcendental communication model. The main conclusion asserts that tawhid functions as a philosophical, normative, and spiritual foundation for the development of an Islamic communication paradigm oriented toward truth, balance, and moral responsibility. These findings open opportunities for further development of communication studies grounded in revelation and spirituality. Abstrak Penelitian ini bertujuan untuk menjelaskan fenomena tauhid sebagai basis komunikasi transendental dalam perspektif Islam, dengan ruang lingkup yang mencakup dimensi teologis, filosofis, dan epistemologis komunikasi. Kajian ini menggunakan pendekatan kualitatif-deskriptif dengan metode analisis literatur terhadap berbagai sumber keislaman klasik maupun kontemporer yang relevan dengan konsep tauhid dan komunikasi. Melalui pendekatan ini, penelitian berupaya menemukan korelasi antara kesadaran ketuhanan (tauhid) dengan proses komunikasi manusia sebagai aktivitas spiritual. Hasil kajian menunjukkan bahwa tauhid bukan sekadar doktrin keagamaan, tetapi juga paradigma epistemologis yang menempatkan Tuhan sebagai pusat orientasi komunikasi (theocentric paradigm). Dalam kerangka ini, komunikasi dipahami sebagai proses kesadaran ilahiah yang menghubungkan manusia dengan Tuhan, diri, dan sesama, serta mengandung nilai moral dan etika profetik. Penelitian ini juga menegaskan bahwa paradigma tauhid dapat merekonstruksi teori komunikasi modern yang cenderung antroposentris, menuju model komunikasi yang lebih holistik dan transendental. Kesimpulan utama menyatakan bahwa tauhid berperan sebagai landasan filosofis, normatif, dan spiritual bagi pembentukan paradigma komunikasi Islam yang berorientasi pada kebenaran, keseimbangan, dan tanggung jawab moral. Temuan ini membuka peluang pengembangan lebih lanjut terhadap ilmu komunikasi berbasis wahyu dan spiritualitas.